A Direct Measure of Stand Density Based on Stand Growth. Issue 1 (30th October 2020) - Dean, Thomas J; D'Amato, Anthony W; Palik, Brian J; Battaglia, Mike A; Harrington, Constance A
Abstract: Standardizing gross volume increment on periodic height increment of the dominant trees is a means of minimizing the effects of site quality and age in growth–growing-stock relations; however, volume increment per height increment contains more information than just a normalization method for fitting growth models. This study builds on previous work suggesting that the cumulative sum of the ratios between individual-tree volume increment and height increment may be a direct measure of stand density. We used data from several levels of growing-stock studies for Douglas-fir, ponderosa pine, and red pine to explore this hypothesis. Regression analysis indicated that the sum of the ratios is proportional to( D q x ⋅ N ), the underlying equation form of Reineke's stand density index. Stem growth is a function of canopy dynamics, and additional analyses showed that volume added per unit of height growth was also related to canopy architecture, increasing with decreasing live-crown ratio and increasing foliage density. The linkages between growth, canopy architecture, intermediary canopy dynamics, and ( D q x ⋅ N ) support the hypothesis that the sum of the tree ratios between volume increment and height increment is a direct measure of site occupancy due to its association between growth and corresponding resource use.